2015
DOI: 10.1120/jacmp.v16i6.5618
|View full text |Cite
|
Sign up to set email alerts
|

Intensity‐modulated radiotherapy versus proton radiotherapy versus carbon ion radiotherapy for spinal bone metastases: a treatment planning study

Abstract: Outcomes for selected patients with spinal metastases may be improved by dose escalation using stereotactic body radiotherapy (SBRT). As target geometry is complex, we compared SBRT plans using step‐and‐shoot intensity‐modulated radiotherapy (IMRT), carbon ion RT, and proton RT. We prepared plans treating cervical, thoracic, and lumbar metastases for three different techniques — IMRT, carbon ion, and proton plans — to deliver a median single 24 Gy fraction such that at least 90% of the planning target volume (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…In this study, we found that carbon ion radiation changed the metabolite secretion of irradiated cells, thus affecting the biological behavior of unirradiated cells. Generally, X-rays promote migration and invasiveness under normoxic conditions, and carbon ions can significantly reduce migration ( 27 ) and invasion of tumor cells in vitro and vivo ( 23 , 28 ). Further, we used metabonomic analysis to confirm that the culture medium collected from carbon ion irradiated WI-38 cells is related to the decrease of metastatic potential of A549 cells.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that carbon ion radiation changed the metabolite secretion of irradiated cells, thus affecting the biological behavior of unirradiated cells. Generally, X-rays promote migration and invasiveness under normoxic conditions, and carbon ions can significantly reduce migration ( 27 ) and invasion of tumor cells in vitro and vivo ( 23 , 28 ). Further, we used metabonomic analysis to confirm that the culture medium collected from carbon ion irradiated WI-38 cells is related to the decrease of metastatic potential of A549 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that C-ions kill CSCs better than conventional radiotherapy [8,9,10]. Moreover, most of the time, although X-rays promote migration and invasiveness under normoxia [11], C-ions produce a significant benefit by decreasing the migration and invasiveness of cancer cells in vitro [11,12] and in vivo [13,14]. Conversely, a few studies report anti-invasive capacities in response to X-rays, whereas C-ions can be pro-invasive [15].…”
Section: Introductionmentioning
confidence: 99%
“…Many cancers result in metastasis in the spinal vertebrae, which can cause pain, neurological disability, and reduce quality of life [1,2]. To improve the local disease control and relieve symptoms, radiosurgery could be used for the primary treatment of spinal metastases [3][4][5]. Compared to the standard radiotherapy, Stereotactic body radiosurgery/radiotherapy (SBRS/SBRT) delivers a much higher dose to the tumor in fewer treatment fractions while minimizing the unnecessary dose to the healthy tissues.…”
mentioning
confidence: 99%